Financial and Economic Policy of The Russian Occupation Regime in Eastern Galicia and Northern Bukovina during the First World War: Modern Scientific Discourse - Orlyk, Svitlana; Tsyganenko, Liliia (Journal of Danubian Studies and Research, 2022)
The article analyses the degree of research in Ukrainian historical science of the problems of the financial and economic policy of the Russian occupation regime in Eastern Galicia and Northern Bukovina during the First World War. The author places special emphasis on the achievements and tasks of modern domestic historical science in this issue.